Trichoderma reesei FS10-C enhances phytoremediation by Sedum plumbizincicola for Cd-contaminated soils and associated soil microbial activities - Ying eTeng; Yang eLuo; Wenting eMa; Lingjia eZhu; Wenjie eRen; Yongming eLuo; Yongming eLuo; Zhengao eLi (Frontiers in Plant Science, 2015)
This study aimed to explore the effects of Trichoderma reesei FS10-C on the phytoremediation of Cd-contaminated soil by Sedum plumbizincicola as well as soil fertility. After characterizing the Cd tolerance of T. reesei FS10-C, a pot experiment was carried out to investigate the plant growth and Cd uptake of S. plumbizincicola with the addition of inoculation agents with/without T. reesei FS10-C. The soil samples in pots were analyzed for pH, available phosphorus (P), microbial biomass C, enzyme activities, microbial community functional diversity and Trichoderma colonization ability. The results indicated that FS10-C possessed high Cd resistance up to 300 mg L-1. All inoculation agents enhanced the biomass of plant shoots by 6-53% fresh weight and 16-61% dry weight as well as Cd uptake in plant shoots by 10-53% compared with the control. In addition, soil biomass C, enzyme activities and microbial community evenness were all increased to varying degrees by all inoculation agents, indicating that soil microbial biomass and activities were both enhanced. It was also found that the two inoculation agents accompanied by FS10-C were better compared with the inoculation agents without FS10-C on all accounts, from which it could be concluded that T. reesei FS10-C was effective in improving Cd phytoremediation of S. plumbizincicola and soil fertility. Furthermore, among all the inoculation agents, solid fermentation powder of FS10-C demonstrated the greatest capacity to enhance plant growth, Cd uptake, nutrient release, and microbial biomass and activities, as indicated by its superior ability to colonize Trichoderma. Thus, we could also conclude that solid fermentation powder of FS10-C was a good candidate for use as an inoculation agent for T. reesei FS10-C to improve the phytoremediation of Cd-contaminated soil and soil fertility.